2020
DOI: 10.1016/j.jtbi.2020.110419
|View full text |Cite
|
Sign up to set email alerts
|

A type IV functional response with different shapes in a predator–prey model

Abstract: The version presented here may differ from the published version or from the version of the record. Please see the repository URL above for details on accessing the published version and note that access may require a subscription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…where is expressed in Eq. (41). Then x((n + k)T) > x(nT) k → ∞ as k → ∞, which contradicts the boundedness of x(t).…”
Section: Extinction and Permanencementioning
confidence: 93%
See 1 more Smart Citation
“…where is expressed in Eq. (41). Then x((n + k)T) > x(nT) k → ∞ as k → ∞, which contradicts the boundedness of x(t).…”
Section: Extinction and Permanencementioning
confidence: 93%
“…Some interesting functional responses, widely used in predator-prey models, are Holling type, sigmoid type and Beddington-DeAngelis functional responses. More details as regards the functional responses can be found in [23,[39][40][41]. However, the generalized Holling type IV functional response or the Monod-Haldane function [5,[42][43][44][45]…”
Section: Introductionmentioning
confidence: 99%
“…As we consider a predator-prey model with group defense in the prey, we use the kinetic equations developed in Köhnke et al (2020)…”
Section: Model and Methodsmentioning
confidence: 99%
“…Recently, a series of mathematical models has been developed to better understand the dynamics of the predator-prey system with different kinds of functional responses [6,[16][17][18][19][20][21][22][23][24]. Dalziel et al [16] studied a modified Holling type-II predator-prey model, based on the premise that the search rate of predators is dependent on the prey density, rather than constant.…”
Section: Introductionmentioning
confidence: 99%
“…ey also defined the basic reproduction number R 0 and show that it is a threshold parameter determining whether the predators can coexist with the prey species. Kohnke et al [18] studied a predatorprey model and developed a functional response using timescale separation. In their study, they showed that the resulting functional response contains a single parameter that controls whether the group defense functional response is saturating or dome-shaped.…”
Section: Introductionmentioning
confidence: 99%